Rainforests as reservoirs for economically important pollinators, the stinglees bees, Trigona SPP - Sajap, Ahmad Said (Jabatan Perhutanan Semenanjung Malaysia, 2010)
Tropical rainforests are the most biologically rich and diverse forests in the world. These forests support the greatest abundance of life forms and insects are by far the most diverse and abundant life forms. They inhabit all niches of the forest habitats while serving key roles in the ecological functions of the forests. One of the most important ecological roles of insects is pollination. Cross-pollination process involving insects allows forest regeneration and maintenance of their genetic diversity.A wide range of tropical trees are largely pollinated by insects. These services are provided by bees, flies, wasps, butterflies, moths, midges, thrips and beetles. Significant roles of bees, especially the stingless bees, Trigona (Apidae: Melipoini) in pollination have been highlighted in many studies. These stingless bees thrive predominantly on flowers in the forests and forest borders. A rapid survey conducted using honey-water spraying in two forest reserves in Pahang recorded 12 species. Recently, attempts were made to introduce two species of Trigona which are T. thoracica and T. apicalis, in strawberry, rock melons and longan farms to facilitate pollination. The impact of these pollinators on the yield of the crops has yet to seen. Results from elsewhere have proven that introduction of Trigona into cropping systems significantly increased quality and yield of the respective crops. In Malaysia, despite the abundance of Trigona species available in our forests, their potential in enhancing horticultural yields has yet to be realized. In recent years, however, a decline in pollinator diversity was recorded in many parts of the world. The loss of this "free ecological service" might also impair productivity of the forest and agriculture. In order to sustain pollinator services associated with agricultural and forest ecosystems, a greater understanding is needed of the multiple goods and services provided by pollinator diversity and the factors that influence their decline and activity. A management program that promotes the conservation and diversity of these pollinators through restoration of natural areas necessary to optimize pollinator services in agricultural and other terrestrial ecosystems is highly warranted.